Combined fixation of modular tumor proximal humeral endoprosthesis (experimental and clinical study) - Vyrva, Oleg; Mikhanovsky, Dmytro; Karpinsky, Mykhaylo; Nikolchenko, Olga (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Objective: to substantiate, develop and implement a more reliable combined endoprosthesis fixation system for replacement of postresectional defects of the proximal humerus, reduction in the number of complications from the endoprosthesis and improvement of the results of tumor joint replacement. Methods: finite element models of the «endoprosthesis – humerus» system with different fixation methods (combined and intramedullary only) have been developed, investigated for tension, bending and twisting. In an experiment on 20 white rats, the situation was modeled after tumor resection of the long-bone diaphysis and replacement of the defect with a modular endoprosthesis. The animals were divided into two groups: in the experimental, an endoprosthesis was installed with a combined fixation system, in the control one — with intramedullary. Twelve patients with tumor lesion of the proximal humerus were operated: in 3 an endoprosthesis with intramedullary fixation was implanted, in 9 patients with a combined implant. The observation period is up to 7 years. Results: on mathematical models it is determined that the use of an additional fixation system can significantly reduce the load on the «critical zone» due to its redistribution to extracortical plates. In vivo experiment, the stability of fixation and a significant reduction in the number of complications with the use of combined fixation was demonstrated. On the basis of the theoretical and experimental data obtained, the proximal humeral endoprosthesis with a combined fixation system was developed and implemented into practice. In patients operated on with the proposed fixation system, complications associated with the endoprosthesis were not revealed. Conclusions: the use of the developed endoprosthesis with extra-cortical fixation to replace the post-exposure defects of the proximal humerus makes it possible to reduce the risk of complications associated with the implant.